Articulated Maintenance : Improving maintainability for the nextgenerations of Volvo CE’s articulated haulers - Præsto, Richard (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2017)
This is a project performed by me, Richard Præsto, student at Luleå University ofTechnology, with the intentions to suggest an improvement for the maintenancesystem of Volvo Construction Equipment’s articulated haulers. Today, themaintenance process consists of several different maintenance points and isperformed by maintenance technicians all over the world – but since the machinesneed to be taken out of production in order to receive maintenance, the processneeds to be quick. By researching documents, performing field studies and testingnew ideas, several different solutions were found and evaluated, to eventually befiltered down to one final concept. The final concept, which suggested animprovement of the engine oil and engine filter exchange processes, lived up to theexpectations by fulfilling the project goals and objectives. It was concluded that thesolution was a clear improvement and that it was also applicable to the whole rangeof the VCE machines.